The impact of macroeconomic variable towards inflation rate in Malaysia / Florissa Linang - Linang, Florissa (Faculty of Business and Management, 2018)
The literature about inflation indicates that the economists have spent plenty of time to understand the reasons that cause inflation. The economists have succeeded to give details about the sources of the inflation. But, until now the relation of the inflation and the other macroeconomic variables such as the government expenditures has remained debatable. The aim of this study is to investigate the impact of macroeconomics variables towards inflation rate in Malaysia. The selected macroeconomic variables or the independent variables used are government spending, money supply and unemployment for period from 1986 to 2016, where the total number of observation is 31, while the dependent variable is inflation rate. The relationship is examined by undertaking regression analysis using time series data that collected from World Bank Database. Both Single Linear Regression and Multiple Linear Regression are used to identify the relationship between dependent and independent variables. From the result, the study shows that government spending and unemployment rate has negative insignificant relationship towards inflation meanwhile; money supply has negative significant relationship towards inflation. This indicates that money supply give impacts towards inflation while government spending and unemployment does not give impact to inflation rate in Malaysia. The relationship discovered should be useful for public, industries and policy makers as well.